2014
DOI: 10.3892/ijo.2014.2325
|View full text |Cite
|
Sign up to set email alerts
|

Pristimerin, a quinonemethide triterpenoid, induces apoptosis in pancreatic cancer cells through the inhibition of pro-survival Akt/NF-κB/mTOR signaling proteins and anti-apoptotic Bcl-2

Abstract: Lack of effective therapeutics for pancreatic cancer at the present time underscores the dire need for safe and effective agents for the treatment of this malignancy. In the present study, we have evaluated the anticancer activity and the mechanism of action of pristimerin (PM), a quinonemethide triterpenoid, against MiaPaCa-2 and Panc-1 pancreatic ductal adenocarcinoma (PDA) cell lines. Treatment with PM inhibited the proliferation and induced apoptosis in both cell lines as characterized by the increased Ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 34 publications
0
66
0
1
Order By: Relevance
“…It was noted that the increase in Bax/Bcl-2 ratio was mainly due to the down-regulation of Bcl-2 at protein level, but not at the mRNA level. Thus, it is suggested that Bcl-2 protein is posttranslationally modified by either phosphorylation or ubiquitination via MAPKs and AKT, resulting in a proteosomal degradation of Bcl-2 protein which increases the BAX/BCL-2 ratio to initiate the mitochondrial apoptotic pathway (Deeb et al, 2014;Liu et al, 2013;Gao and Dou, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that the increase in Bax/Bcl-2 ratio was mainly due to the down-regulation of Bcl-2 at protein level, but not at the mRNA level. Thus, it is suggested that Bcl-2 protein is posttranslationally modified by either phosphorylation or ubiquitination via MAPKs and AKT, resulting in a proteosomal degradation of Bcl-2 protein which increases the BAX/BCL-2 ratio to initiate the mitochondrial apoptotic pathway (Deeb et al, 2014;Liu et al, 2013;Gao and Dou, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] So, the recovery of pristimerin from Celastrus orbiculatus has strong potential in pharmaceutical industry. The chemical structure of pristimerin is shown in Fig.…”
Section: )mentioning
confidence: 99%
“…In addition, several studies have reported that pristimerin possesses potent anti-cancer effect [7][8][9][10][11][12]. The mechanism of anticancer activity of pristimerin was mainly involved in suppressing the formation of proteasomes [13], downregulation of NF-κB activity and cyclin D1 expression, and activation of Bax, caspase, and PARP-1 [9,13,14]. Therefore, pristimerin has the potential of becoming a lead compound in anti-cancer drugs.…”
Section: Introductionmentioning
confidence: 97%
“…Some research articles have found that pristimerin and its biological analog URB602 are inhibitors of monoglyceride lipase, which could help us better understand the function of monoglyceride lipase [5,6]. In addition, several studies have reported that pristimerin possesses potent anti-cancer effect [7][8][9][10][11][12]. The mechanism of anticancer activity of pristimerin was mainly involved in suppressing the formation of proteasomes [13], downregulation of NF-κB activity and cyclin D1 expression, and activation of Bax, caspase, and PARP-1 [9,13,14].…”
Section: Introductionmentioning
confidence: 98%